2021
DOI: 10.1007/s40544-021-0497-1
|View full text |Cite
|
Sign up to set email alerts
|

Review of research on loosening of threaded fasteners

Abstract: Loosening of threaded fasteners is a key failure mode, which is mainly caused by the slippage and friction behaviors on the thread and bearing surfaces, and will affect the integrity and reliability of products. Numerous scholars have conducted research on the loosening of threaded fasteners; however, comprehensive reviews on the loosening of threaded fasteners have been scarce. In this review article, we define loosening as a loss of preload and divide it into non-rotational and rotational loosening. The caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 99 publications
1
16
0
Order By: Relevance
“…Sakai 3 analyzed the effect of external axial cyclic loading and concluded that bolt rotation loosening was caused by bolt radial contraction and nut expansion. Gong et al 4 summarized the causes and mechanisms of non-rotational and rotational loosening. He deemed that transverse vibration was the main cause of bolt rotation loosening and believed that the bolt rotation loosening would occur when the static friction between threads was overcome, and if the inertial force of transverse vibration load was greater than the static friction, then rotational loosening of the threads occurred.…”
Section: Introductionmentioning
confidence: 99%
“…Sakai 3 analyzed the effect of external axial cyclic loading and concluded that bolt rotation loosening was caused by bolt radial contraction and nut expansion. Gong et al 4 summarized the causes and mechanisms of non-rotational and rotational loosening. He deemed that transverse vibration was the main cause of bolt rotation loosening and believed that the bolt rotation loosening would occur when the static friction between threads was overcome, and if the inertial force of transverse vibration load was greater than the static friction, then rotational loosening of the threads occurred.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of bolt loosening have been summarized as the slippage, fretting wear and repeated plastic deformation [1]. Many studies have focused on different methods to avoid bolt loosening initiated by the slippage behavior on the thread surface, which called rotational loosening.…”
Section: Introductionmentioning
confidence: 99%
“…High-strength titanium alloys are widely used for aircraft fasteners due to their strong ability to lose weight, excellent corrosion resistance, cold formability, and good compatibility with composite materials. For high-strength titanium alloy fasteners, fretting damage, as one of the common damage failure modes of aircraft fasteners, is the key factor restricting their reliability and service life . According to the statistics from the United States Air Force, fretting damage accounts for over one-sixth of damage in aero-engines, especially reducing the fatigue limit to only one-third of the ordinary fatigue limit. Hence, a number of researchers have paid extensive attention to fretting damage in titanium alloys. …”
Section: Introductionmentioning
confidence: 99%